Pengaruh Gaya Mengajar Resiprokal Terhadap Gerak Dasar Pada Pukulan Forehand Push Dalam Permainan Tenis Meja Terhadap Peserta Didik Kelas X SMA Negeri 1 Tondano - Jitro Yoga Dharma Parandangan; A.R.J Sengkey; Yuliana Sattu (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Reciprocal style is a teaching style where students have the opportunity to give feedback to their peers or partners. This allows students to improve their learning outcomes and increase social interaction with their peers. Table tennis games that are usually taught in schools have the aim that students can have knowledge and understanding of table tennis itself and can develop sportsmanship and actively participate in table tennis learning. The method in this research is experimental method. The population in this study were students of class X SMAN 1 Tondano which amounted to 172 students. The sample used in this study was 26 students of class X who were divided into two groups, namely the experimental group of 13 students and the control group of 13 students. The conclusion of this study is that the application of reciprocal style can have an influence on basic movements on forehand push shots in table tennis games on basic movements on forehand push shots in table tennis games for students of SMA Negeri 1 Tondano.